Advances in Differential Equations and Applications - Casas, Fernando; Martínez, Vicente; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The book contains a selection of contributions given at the 23rd Congress on Differential Equations and Applications (CEDYA) / 13th Congress of Applied Mathematics (CMA) that took place at Castellon, Spain, in 2013. CEDYA is renowned as the congress of the Spanish Society of Applied Mathematics (SEMA) and constitutes the main forum and meeting point for applied mathematicians in Spain. The papers included in this book have been selected after a thorough refereeing process and provide a good summary of the recent activity developed by different groups working mainly in Spain on applications of mathematics to several fields of science and technology. The purpose is to provide a useful reference of academic and industrial researchers working in the area of numerical analysis and its applications.
1 A. Balaguer-Beser, M.T. Capilla, B. Nácher-Rodríguez, F.J. Vallés-Morán and I. Andrés-Doménech. A high-order well-balanced central scheme for the shallow water equations in channels with irregular geometry -- 2 J. Cerdán, J. Marín and J. Mas. A block compression algorithm for computing preconditioners -- 3 C. Gorria, M. Lezaun, D. Pardo, E. Sáinz de la Maza, D. Bilbao, I. Gutiérrez and M. Lueches. Optimising the welding process in the manufacture of offshore mooring chains -- 4 G. Pagnini. Fire spotting effects in wildland fire propagation -- 5 L. Ferragut, M. Isabel Asensio, J. Manuel Cascón and Diego Prieto. A simplified wildland fire model applied to a real case -- 6 P. González de Alaiza Martínez and M.E. Vázquez-Cendón. Operator-splitting on hyperbolic balance laws -- 7 V.J. Bolós and R. Benítez. The wavelet scalogram in the study of time series -- 8 J. Casado-Díaz, J. Couce-Calvo, F. Maestre and J.D. Martín-Gómez. A corrector result for the wave equation with high oscillating periodic coefficients -- 9 A. Barreras and J.M. Peña. On tridiagonal sign regular matrices and generalizations -- 10 J.M. Arrieta, R. Pardo and A. Rodríguez-Bernal. A degenerate parabolic logistic equation -- 11 A. Jiménez-Casas and A. Rodríguez-Bernal. A model of traffic flow in a network -- 12 F. Aràndiga and J.J. Noguera. Signal denoising with Harten's multiresolution using interpolation and least squares fitting -- 13 F. Aràndiga and D.F. Yáñez. On multiresolution transforms based on weighted-least squares -- 14 A. Rodríguez-Bernal and S. Sastre Gómez. Nonlinear nonlocal reaction-diffusion equations -- 15 B. Campos and P. Vinel. Building nonsingular Morse-Smale flows on 3-dimensional lens spaces -- 16 M.T. González Montesinos and F. Ortegón Gallego. Weak solutions to a nonuniformly elliptic EDPs system in the harmonic regime -- 17 L.J. Álvarez-Vázquez, A. Martínez, C. Rodríguez, M.E. Vázquez-Méndez and M.A. Vilar. Optimal control of sedimentation in rivers and canals -- 18 M. Isabel García-Planas and S. Tarragona. Control problems on time-invariant singular linear systems -- 19 C. Quesada and A. Rodríguez-Bernal. Perturbation of analytic semigroups in uniform spaces in R^N -- 20 V. Carmona, F. Fernández-Sánchez and E. García-Medina. Existence of homoclinic and heteroclinic connections in continuous piecewise linear systems -- 21 J.M. Arrieta, M. Villanueva-Pesqueira. Fast and slow boundary oscillations in a thin domain -- 22 M. Canadell and A. Haro. Parameterization method for computing quasi-periodic reducible normally hyperbolic invariant tori -- 23 I. Cordero-Carrión and P. Cerdá-Durán. Partially implicit Runge-Kutta methods for wave-like equations -- 24 C.M. Campos. Higher order variational integrators: a polynomial approach -- 25 J.A. López Ortí, F.J. Marco Castillo and M.J. Martínez Usó. Study of errors in the integration of the two-body problem using generalized Sundman's anomalies -- 26 A. Arnal, C. Chiralt and F. Casas. Analytic approximations for linear differential equations with periodic or quasi-periodic coefficients.
Keywords: Differential equations; Partial differential equations; Numerical analysis; Dynamics; Ergodic theory; Ordinary Differential Equations; Partial Differential Equations; Numerical Analysis; Dynamical Systems and Ergodic Theory